Dramaturgia barw w Zaginionej dziewczynie Davida Finchera - Choczaj, Małgorzata (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2015)
The Dramaturgy of Colour in David Fincher’s Gone Girl The article is an analysis of colour symbolism in David Fincher’s Gone Girl where yellow, blue and green are symbols of marital breakdown. Colours and their contrasts emphasize competing versions of events in the film and emotional conflicts between the characters. The text refers to the psychology of visual perception and Susanne Marschall’s idea of colour playing a dramatic, symbolic and emotional role in the film.